The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fcell.2021.791758
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Players for Inter-Organelle Communication: PI5P4Ks and Their Lipid Product PI-4,5-P2 Come to the Surface

Abstract: While organelles are individual compartments with specialized functions, it is becoming clear that organellar communication is essential for maintaining cellular homeostasis. This cooperation is carried out by various interactions taking place on the membranes of organelles. The membranes themselves contain a multitude of proteins and lipids that mediate these connections and one such class of molecules facilitating these relations are the phospholipids. There are several phospholipids, but the focus of this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 81 publications
2
6
0
Order By: Relevance
“…Drug treatment up-regulated the expression of differentiation markers and induced morphological changes compatible with a more differentiated phenotype (Supplementary Figure 2). Our results are in line with a recent study suggesting PIP4K2s be involved in the regulation of organelle crosstalk as well as the preservation of metabolic homeostasis [18]. The minimal effects observed in healthy CB CD34 + cells suggest that THZ-P1-2 may have a favorable therapeutic window.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Drug treatment up-regulated the expression of differentiation markers and induced morphological changes compatible with a more differentiated phenotype (Supplementary Figure 2). Our results are in line with a recent study suggesting PIP4K2s be involved in the regulation of organelle crosstalk as well as the preservation of metabolic homeostasis [18]. The minimal effects observed in healthy CB CD34 + cells suggest that THZ-P1-2 may have a favorable therapeutic window.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, THZ-P1-2 reduced cell viability by disrupting mitochondrial homeostasis, cellular metabolism, and autophagy. The role of PIP4K2s in the regulation of energy metabolism and autophagy has been previously reported, in particular, the product of these enzymes, PI-4,5-P 2 , has been described as necessary for the fusion of lysosomes with autophagosomes and to complete the autophagic flux [16,18,26]. Considering our data, THZ-P1-2 was able to accurately phenocopy many of the cellular and molecular findings observed in PIP4K2s genetic inhibition models, including accumulation of SQSTM1/p62 and LC3BII [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, THZ-P1-2 reduced cell viability by disrupting mitochondrial homeostasis, cellular metabolism, and autophagy. The role of PIP4K2s in the regulation of energy metabolism and autophagy has been previously reported; in particular, the product of these enzymes, PI-4,5-P 2 , has been described as necessary for the fusion of lysosomes with autophagosomes and to complete autophagic flux [ 16 , 18 , 26 ]. Considering our data, THZ-P1-2 was able to accurately phenocopy many of the cellular and molecular findings observed in PIP4K2s genetic inhibition models, including accumulation of SQSTM1/p62 and LC3BII [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, PI-4,5-P 2 -mediated signaling is implicated in many cellular processes, including proliferation, survival, glucose uptake, and cytoskeletal organization, which have been reported to be deregulated in breast cancer, acute leukemias, glioblastoma, and soft tissue sarcomas [ 13 , 18 ]. Cancer genomic and transcriptomic landscape studies have revealed that PIP4K2-related genes are usually not mutated, but their expression is frequently altered [ 13 ].…”
Section: Introductionmentioning
confidence: 99%